1976
DOI: 10.1017/s0016756800043223
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the Wolstonian Stage of the British Pleistocene

Abstract: SummaryThe lithostratigraphical division of the Wolstonian Stage of the British Pleistocene is reviewed in the light of borehole records along the line of the M 69 motorway. The Wolston Clay is divided into 5 members. The evidence from the M 69 shows that 2 periods of glacier advance were separated by a major period of recession of the order of 104 years, in which most of the sediments of Glacial Lake Harrison were deposited. It is argued that this recession was interstadial rather than interglacial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…Critically, the glaciogenic deposits upon which the Wolstonian Glaciation was identified were shown in Perrin et al (1979) to be part of the same association of deposits as those considered to be of Anglian age further east, and the associated Wolstonian fluviatile deposits that underlie the glaciogenic sediment have been shown to be pre-Anglian in age (Rose, 1987(Rose, , 1994 rather than younger than Anglian as proposed by Shotton (1976Shotton ( , 1983. Traces of other late Middle Pleistocene glaciations were still identified at specific localities in east Lincolnshire, Yorkshire and Durham (Catt and Penny, 1966;Davies et al, 2012), and reference to these sites and their significance can be found in Bowen et al (1986) which also allocates the glaciations to geochronometric ages and Marine Isotope Stages.…”
Section: Late Middle Pleistocene Glaciations (Mis 12-6)mentioning
confidence: 93%
See 1 more Smart Citation
“…Critically, the glaciogenic deposits upon which the Wolstonian Glaciation was identified were shown in Perrin et al (1979) to be part of the same association of deposits as those considered to be of Anglian age further east, and the associated Wolstonian fluviatile deposits that underlie the glaciogenic sediment have been shown to be pre-Anglian in age (Rose, 1987(Rose, , 1994 rather than younger than Anglian as proposed by Shotton (1976Shotton ( , 1983. Traces of other late Middle Pleistocene glaciations were still identified at specific localities in east Lincolnshire, Yorkshire and Durham (Catt and Penny, 1966;Davies et al, 2012), and reference to these sites and their significance can be found in Bowen et al (1986) which also allocates the glaciations to geochronometric ages and Marine Isotope Stages.…”
Section: Late Middle Pleistocene Glaciations (Mis 12-6)mentioning
confidence: 93%
“…The main evidence are summarised in Bowen et al (1986) and in Knight et al (2004). Initially, the 'modern' model for glaciation over this period consisted of two lowland glaciations (Mitchell et al, 1973): an earlier Anglian Glaciation equated with the Elsterian of Europe and a Wolstonian Glaciation equated with the Saalian (Shotton, 1976(Shotton, , 1983Straw, 1979) ( Figure 4A) and these are cited in the most recent stratigraphic scheme for the British Quaternary (Bowen, 1999). The Anglian is defined by a stratotype at Corton near Lowestoft in East Anglia (Pointon, 1978) and the Wolstonian by a stratotype at Wolston near Coventry in midland England (Shotton, 1976(Shotton, , 1983) ( Figure 4A).…”
mentioning
confidence: 99%
“…Today the pre-Anglian sequences are confined to central to east East Anglia, where they are grouped as the Ingham Formation (Clarke & Auton, 1984; Hey & Auton, 1988; Gibbard et al, 2013). The stream responsible for this spread was almost certainly a precursor of the East Midlands-derived Trent, as earlier authors concluded (Shotton 1953, 1968, 1976, 1983a,b, 1989; Bishop, 1958; Rice, 1968, 1981, 1991; Rice & Douglas, 1991). This river can be traced upstream northwestwards across the Fenland into southern Lincolnshire, where it may have passed through the Ancaster Gap from the Trent catchment (Fig.…”
Section: Introductionmentioning
confidence: 79%
“…1). Here the late Middle Pleistocene Wolston Formation glacial sediments (and equivalents) of the region overlie deposits of a pre-existing river system, represented by the Baginton–Lillington gravel and sand (members) and its equivalents (Shotton, 1953, 1968, 1976, 1983a,b, 1989; Bishop, 1958; Rice, 1968, 1981, 1991; Rice & Douglas, 1991; Bridge et al, 1998). The fluvial deposits mainly comprise predominantly quartz-rich sediment derived from underlying Triassic bedrock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation